Effect of increasing rudder deflection on rudder inflow for LNG vessel in shallow water - Priyanto, Agoes (2013)
This paper presents the rudder inflow including fully non-uniform wake on a deep drafted LNG vessel in shallow water. The Ansys Fluent v.6.2 software was used to solve Reynold Average Navier-Stokes (RANS) equations, and Icem CFD as a mesh generator. The modeling was conducted based on the B 5-88 type propeller, with a diameter (D) of 7.7 meters. The propeller was meshed using tetra unstructured mesh in a flow field based on 3-Dimension incompressible Navier-stokes solver. It was found in the propeller-to-rudder interaction that there was a slight drop of pressure at rudder leading edge of 00 rudder angle of attack (AoA). However, the dropped pressure was observed on its leading edge as the rudder angle of attack was increased to -70. The effect of increasing rudder deflection was generated by the flow around it and inflows moved over the rudder. This deflection effect continued to X/D=0.4; afterwards, a zero velocity appeared because of the flow encountered by the stagnation region. © (2013) Trans Tech Publications, Switzerland.